Integrating POSDCORB Management and the PERMA Model for Student Well-Being in Inclusive Elementary Schools - Maulida Kafilaturrohmah; Muhammad Zuhaery; Dian Hidayati (Sakura Digital Nusantara, 2026)
The post-pandemic transition has widened the basic literacy gap among early grade students, often triggering academic anxiety and disrupting their psychological well-being. This study analyzes how an inclusive elementary school implemented a scaffolding program to improve student well-being through systematic institutional management. Using a qualitative case study design, the research was conducted at Muhammadiyah Condongcatur Elementary School, Yogyakarta. Data were collected through semi-structured interviews with four key informants: the Deputy Head of Human Resources, the Deputy Head of Curriculum, a first-grade teacher, and a guidance counselor. Data analysis was conducted using thematic coding through ATLAS.ti 9 software. Findings indicate that integrated school governance, characterized by selective staffing, humanistic guidance with gradual reductions in support, and cross-staff coordination, provides a framework that supports targeted pedagogical interventions. Rather than claiming a direct causal relationship, the data suggest that this managerial synergy contextually enables students to achieve incremental “small wins” in reading and writing, thereby fostering a classroom environment attuned to positive emotions, engagement, and achievement. In conclusion, aligning administrative management with adaptive learning support in the classroom is crucial to building a sustainable mental health ecosystem for early grade students facing literacy barriers.